Synergistic Effect of Donor Doping on in-situ Synthesized Co(M)-NiSe2–VSe2 for Battery-Type Supercapacitor and Oxygen Evolution Reaction Applications - Akbar Sial, Qadeer; Mohapatra, Gourab; Basit Ali, Rana; Waqas Khan, Muhammad; Waqas, Muhammad; Kumar, Ashish; Seo, Hyungtak (Chemical Engineering Journal, 2025)
Transition metal selenide materials these days getting attention for their application in hybrid supercapacitor due to their tremendous electrical and band structure properties. However, due to their lower rate performance, significant charge storage performance attenuation, and slow reaction kinetics hampered their applicability. Herein, we have developed ternary selenides of nickel and vanadium with moderate level doping of donor element to produce microflowers consisting of nanosheets. The moderate level of cobalt doping results in enhanced electrical conductivity due to the donor nature of cobalt. Furthermore, composition tuning method was adopted to obtain the excellent electrical, morphological and electrochemical characteristics by varying the concentration of Ni and V. To confirm the experimental results, DFT calculation were performed to analyze the effect of cobalt doping on NiVSe and its effect on the band structure due to which enhanced electrochemical performances were observed. As obtained electrode based on Co(M)-NiVSe showed excellent specific capacity of 2863.38 mAhg−1 at 3 Ag−1. Owing to this much higher specific capacity, asymmetric devices was fabricated, and it showed capacitance retention over 10,000 GCD cycle with the maximum energy and power density 38.73Whkg−1 and 1909.788 Wkg−1 respectively. Additionally, by taking advantage of fabricated electrode, water splitting characteristics were also tested for the OER application. The sample showed overpotential of 199 mV at 10 mAcm−2 with the Tafel slope of 28 mVdec-1. This excellent result is due to the excellent electrochemical properties of synthesized material along with the d-band center engineering and additional states introduce by the presence of cobalt in ternary selenide electrode material.
Keywords: Cobalt doping; Donor-doping; Evolution reactions; Hybrid supercapacitors; In-situ synthesized; Oxygen evolution; Selenides; Structure property; Synergistic effect; Ternary metal selenide; Donor doping; OER; Supercapacitor; Ternary metal selenides